2019
DOI: 10.3390/su11082364
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian-Based NIMBY Crisis Transformation Path Discovery for Municipal Solid Waste Incineration in China

Abstract: Environmental conflicts have been a top global focus and issue for human’s sustainable development. China is confronted with a serious situation with a rigid demand of ecological governance, in which the “Not In My Back Yard” (NIMBY) crisis outbreaks frequently. NIMBY has a great impact on government management and social stability. This study aims to analyze the NIMBY crisis transformation path for municipal solid waste incineration (MSWI) in China. Considering environmental, social and economic influences, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…For a further understanding of the incinerator risk, the identification of the rational state of residents is the most important way to support the government in waste incinerator construction. After that, correct NIMBY knowledge should be induced via insight into the pollution control of the incinerator and the improvement of facilities [13]. This promotes the impact of neighbors on the residents in the non-pseudo-rational state.…”
Section: Decision Strategy For the Changing Of Public Risk Attributementioning
confidence: 99%
See 1 more Smart Citation
“…For a further understanding of the incinerator risk, the identification of the rational state of residents is the most important way to support the government in waste incinerator construction. After that, correct NIMBY knowledge should be induced via insight into the pollution control of the incinerator and the improvement of facilities [13]. This promotes the impact of neighbors on the residents in the non-pseudo-rational state.…”
Section: Decision Strategy For the Changing Of Public Risk Attributementioning
confidence: 99%
“…In this hypothesis, some supporters and centrists seem to follow the residents who are against the construction of waste incineration during social interactions, which leads to conflict with respect to the environmental facility. This behavior is described by the theory of sheep, which was always proposed to describe the herd behavior in many aspects such as changing fashion and occupation choice [13]. Accordingly, it is called the "sheep-flock" effect, a kind of "herd effect", to describe that the individual's ideas or behaviors in a group's interaction will change in the same direction as the majority [17,18].…”
mentioning
confidence: 99%
“…Tough stability maintenance measures intensified public opposition to the NIMBY facility [ 9 ]. Yang et al Integrated Bayesian network structure discovery and co-word analysis into a qualitative analysis, searched data and key factors from a literature search engine with specific themes were used for structure learning, the result confirmed that the Bayesian network model can help government find the path to transform waste NIMBY crisis, which provided a theoretical basis for understanding the transformation of waste NIMBY crisis in China [ 10 ]. Based on this, this paper will further apply relevant theories to answer “why does the waste NIMBY crisis happen?” “How does the waste NIMBY crisis evolve?” Additionally, the scientific validity of the model is verified by a case study.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies focus primarily on the formation mechanism [15] and evolutionary logic of NIMBY conflicts [16] using diachronic analysis, survey study methods or examining the psychology and behaviour of local governments and affected people in decision making in NIMBY projects using specific cases. Governance strategies for NIMBY conflicts have been proposed based on technological improvement, benefit compensation and citizen participation [17,18], but most of them focus on end treatment, and there is little analysis of the NIMBY dilemma from the perspective of public policy.…”
Section: Introductionmentioning
confidence: 99%